Building Holistic Well-Being: Islamic Physical, Psychological, and Spiritual Experiences in Breast Cancer Survivors - Dewi Mustikaningsih; Nurrohmah; Desvika Putridewa Bernanda; Ilham Anugrah Hidayatullah (The Indonesian Institute of Science and Technology Research, 2026)
Breast cancer is a leading cause of death for women in most countries in Indonesia. Breast cancer survivors are the primary subjects of most studies, but little attention is paid to the impact of the procedure, especially the post-mastectomy experience. We examined the physical, psychological, and Islamic spiritual aspects of breast cancer survivors who have undergone mastectomy. In this qualitative study, we recruited 21 women with breast cancer who had undergone mastectomy in a community in West Java Province. Participants were interviewed, recorded, and transcribed verbatim. Thematic analysis was conducted using Atlas-ti7. The main themes that emerged identified physical issues such as pain, fatigue, swelling, numbness, and stiffness at the surgical site; psychological issues such as loss of femininity, low self-esteem, sadness, worry, anxiety, and anger; Islamic spiritual issues such as complaining to Allah SWT, feelings of abandonment, and questioning Allah SWT's supreme power; and Islamic religious spiritual coping. Post-mastectomy breast cancer survivors experienced significant stress due to frequent hospital visits for check-ups and other procedures. We recommend including strategies for overcoming problems in the physical aspect with physical exercise, strategies for overcoming problems in the psychological aspect with breathing exercises, self-talk techniques, strategies for overcoming problems in the Islamic spiritual aspect with prayer, prayer, dhikr, Islamic caring, mindfulness for breast cancer survivors after undergoing mastectomy to improve the overall physical, psychological, and Islamic spiritual well-being.